Merrily we go to hell - Lucas, Cleo 20. Jh; Kopp, Rudolph Georg 1887-1972; Leipold, John 1888-1970 (The Criterion Collection, 2021)
Starring Fredric March and Sylvia Sidney, "Merrily We Go to Hell" is a gripping Pre-Code drama about a rich young woman who falls in love with an abusive alcoholic. Reporter Jerry Corbett (March) aspires to be a playwright but finds himself drinking more than writing. Everyone is stunned when heiress Joan Prentice (Sidney) agrees to marry him - though it initially appears that he has changed his ways. However, when his work takes the couple to New York, Jerry’s bad behavior and a persistent old flame seem to doom their chances for a happy ending. Directed by Dorothy Arzner, one of only a few female directors during the time, and featuring future screen legend Cary Grant in one of his earliest screen appearances, "Merrily We Go to Hell" remains a cautionary tale about desire and addiction. [Cover]